Medical Control at Sports Facilities with Health Opportunities - Nishanov Ilyos Burxanovich; Saidmurodov Samandar (Zien Journals, 2022)
The presented material allows us to show the specifics of medical observation of athletes with disabilities; to assess the functionality of athletes; determine indications and contraindications for sports.
Keywords: sport for persons with disabilities; load dosing; functional state; medical and pedagogical observations